Statin uses in adults with non-dialysis advanced chronic kidney disease: Focus on clinical outcomes of infectious and cardiovascular diseases - Hsiao, Ching-Chung; Yeh, Jih-Kai; Li, Yan-Rong; Sun, Wei-Chiao; Fan, Pei-Yi; Yen, Chieh-Li; Chen, Jung-Sheng; Lin, Chihung; Chen, Kuan-Hsing (Frontiers in Pharmacology, 2022)
3 Abstract Background: Statins are commonly used for cardiovascular disease (CVD) prevention. Observational studies reported effects on sepsis prevention and mortality improvement. Patients with chronic kidney disease (CKD) are at high risk for CVD and infectious diseases. Limited information is available for statin use in patients with non-dialysis CKD stage V. Method: The retrospective observational study included patients with non-dialysis CKD stage V, with either de novo statin use or none. Patients who were prior statin users and had prior cardiovascular events were excluded. The key outcomes were infection related hospitalizations, major adverse cardiovascular events (MACE) (non-fatal myocardial infarction, hospitalizations for heart failure or non-fatal stroke), and all-cause mortality. The data was retrieved from the Chang Gung Research Database (CGRD) from January 2001 to December 2019. Analyses were conducted with Cox proportional hazard regression models in the propensity score matching (PSM) cohort. Result: A total of 20352 patients with CKD stage V were included (1431 patients were defined as de novo statin users). After PSM, 1318 statin users were compared with 1318 non-users. The infection-related hospitalizations (IRH) rate was 79.3 versus 94.3 per 1000 person-years in statin users and non-users, respectively with a hazard ratio (HR) (0.83, 95% confidence interval (CI) 0.74-0.93, p=0.002). The incidence of MACE was 38.9 versus 55.9 per 1000 person-years in statin users and non-users, respectively (HR, 0.72; 95% CI 0.62-0.83, p<0.001). The all-cause mortality did not differ between statin users and non-users, but statin users had lower infection-related mortality than non-users (HR, 0.59; 95% CI 0.38-0.92, p=0.019). Conclusion: De novo use of statin in patients with non-dialysis CKD stage V reduced the incidence of cardiovascular events, hospitalization and mortality for infectious disease. The study results reinforced the benefits of statin in a wide range of patients with renal impairment before maintenance dialysis.